The neuropeptide 26RFa in the human gut and pancreas: potential involvement in glucose homeostasis. Issue 7 (July 2019) - Prévost, Gaëtan; Picot, Marie; Le Solliec, Marie-Anne; Arabo, Arnaud; Berrahmoune, Hind; El Mehdi, Mouna; Cherifi, Saloua; Benani, Alexandre; Nédélec, Emmanuelle; Gobet, Françoise; Brunel, Valéry; Leprince, Jérôme; et al.
Abstract : Objective: Recent studies performed in mice revealed that the neuropeptide 26RFa regulates glucose homeostasis by acting as an incretin and by increasing insulin sensitivity. However, in humans, an association between 26RFa and the regulation of glucose homeostasis is poorly documented. In this study, we have thus investigated in detail the distribution of 26RFa and its receptor, GPR103, in the gut and the pancreas, and determined the response of this peptidergic system to an oral glucose challenge in obese patients. Design and methods: Distribution of 26RFa and GPR103 was examined by immunohistochemistry using gut and pancreas tissue sections. Circulating 26RFa was determined using a specific radioimmunoassay in plasma samples collected during an oral glucose tolerance test. Results: 26RFa and GPR103 are present all along the gut but are more abundant in the stomach and duodenum. In the stomach, the peptide and its receptor are highly expressed in the gastric glands, whereas in the duodenum, ileum and colon they are present in the enterocytes and the goblet cells. In the pancreatic islets, the 26RFa/GPR103 system is mostly present in the β cells. During an oral glucose tolerance test, plasma 26RFa profile is different between obese patients and healthy volunteers, and we found strong positive correlations between 26RFa blood levels and the BMI, and with various parameters of insulin secretion and insulin resistance. Conclusion: The present data suggest an involvement of the 26RFa/GPR103 peptidergic system in the control of human glucose homeostasis.